Imaging Findings and Prevalence of Central Precocious Puberty at Siriraj Hospital - Sopa Pongpornsup; Orasa Chawalparit; Preeyacha Pacharn (Siriraj Medical Journal, 2003)
Central precocious puberty occurs as a result of premature pituitary stimulation and increased secretion of gonadotropins. The differential diagnosis of true precocious puberty includes cerebral and idiopathic categories. This differentiation, which cannot be made endocrinologically due to similarities in pituitary gonadotropin and sex steroid levels, may facilitatic by Magnetic Resonance Imaging (MRI) of the brain. Objective : To analyze MR imaging findings and incidence of each pathology in central precocious puberty, and to compare pituitary height in patients with central precocious puberty with patients in a control group. Materials and methods : A retrospective study of central precocious puberty in 22 patients was performed from March 2002 to July 2003. The control group consisted of 54 boys and 46 girls. Analyzed parameter included pituitary height, shape and posterior bright spot. The shape was assessed by a pituitary grading system which was based on the concavity of the upper pituitary surface (grade 1 = marked concavity, grade 2 = mild concavity, grade 3 = flat, grade 4 = mild convexity, grade 5 = marked convexity). Bone age, and pelvic ultrasonography were evaluated in the study group. Results : Twenty two children with central precocious puberty (4 boys and 18 girls) were divided into two subgroup according to MRI findings as follows : idiopathic 15 patients (68.18%) and noidiopathic 7 patients (3 patients had nodule at pituitary stalk, 2 had microadenoma, 1 had germ cell tumour at pinealgland, and 1 had hypothalamic harmatoma). The mean pituitary height in the study group was 5.59 mm (SD 1.7). The mean height of the control group was 5.25 mm. There was significant difference among the two groups (p < 0.005). Conclusion : The most common cause in central precocious puberty is idiopathic. However the MRI is necessary to necessary to excluding the surgical cause as tumor. Pituitary height of more than 5.25 mm may be a helpful variable for follow up the result of medical treatment in precocious children.